Kolaborasi Antarnegara Pembelajaran Klinis menuju Industri 5.0 - Ainun Ganisia; Elga Caecaria Grahardika Andani; Rakhmalia Imeldawati; Nurul Fathiyyah (Rena Cipta Mandiri, 2026)
Clinical learning development in health professional education requires collaboration across institutions and countries to respond to the needs of Industry 5.0, which emphasizes technology, patient safety, and a human-centric approach. This community service program aimed to strengthen international collaboration networks for the introduction and development of clinical learning. The program consisted of partner coordination, needs assessment, international seminar, focus group discussion, clinical learning 5.0 workshop, pre-test and post-test evaluation, and preparation of a follow-up roadmap. Participants represented international higher education networks and clinical practice partners. The results indicated improved participant understanding of clinical learning 5.0, clinical supervision, assessment, reflective learning, patient safety, tele-preceptorship, and digital platform utilization. The program also produced a draft article, webinar documentation, a brief module, and a draft collaboration roadmap. This activity strengthened the foundation for more structured, sustainable, and adaptive academic-clinical partnerships in global health education.